Geocerthia, a new genus of terrestrial ovenbird (Aves: Passeriformes: Furnariidae) - Chesser, R. Terry; Claramunt, Santiago; Derryberry, Elizabeth; Brumfield, Robb T. (Zootaxa, 2009)
The avian genus Upucerthia was until recently considered to consist of nine species (Sibley and Monroe 1990, Dickinson 2003, Remsen 2003) of mainly terrestrial ovenbirds, commonly known as earthcreepers. Recent molecular studies of the genus (Chesser et al. 2007, Fjeldså et al. 2007) indicated that Upucerthia, as traditionally constituted, was highly polyphyletic, its nine species apparently belonging to four distinct lineages. Four species of Upucerthia – albigula, jelskii, validirostris, and the name-bearing species dumetaria – formed a well-supported clade sister to Cinclodes (Chesser et al. 2007, Fjeldså et al. 2007). Of the five other species of Upucerthia, U. andaecola and U. ruficaudus formed a clade with Eremobius phoenicurus and Chilia melanura, all of which were subsequently transferred to the genus Ochetorhynchus (Chesser et al. 2007, Fjeldså et al. 2007). Upucerthia harterti and U. certhioides formed a distinct clade and were placed in the newly erected genus Tarphonomus (Chesser and Brumfield 2007). The position of the final species, U. serrana, was not well resolved, although it appeared to form part of a clade including the genera Cinclodes and Upucerthia sensu stricto (Chesser et al. 2007, Fjeldså et al. 2007).